Implementation of jigsaw learning to improve mathematics learning outcomes of grade IV elementary school - Diah Rizki Nur Kalifah; Ali Nasrullah; Badlihisham Mohd Nasir; Zingiswa Mybert Monica Jojo (Universitas Papua, 2025)
The low learning outcomes of mathematics at the primary school level, especially among fourth-grade students, are a major concern in the world of education. Despite numerous efforts to enhance the comprehension of mathematical concepts, the outcomes remain unsatisfactory. The purpose of the study was to explore the application of the jigsaw model in improving mathematics learning outcomes in grade IV. The type of research is classroom action research (CAR), with a Kemmis and Taggart model design, consisting of two cycles. Each cycle includes four stages: planning, implementation, observation, and reflection. The research subjects were 12 fourth-grade students, and data collection techniques were conducted through observation, tests, and documentation. Data analysis was conducted using the descriptive analysis method, using descriptive statistical formulas such as frequency distribution and average. The findings showed that the application of the jigsaw model succeeded in improving the learning outcomes of fourth-grade students, as evidenced by the percentages of 43% in cycle I and 89% in cycle II. Therefore, we conclude that the application of this model effectively enhances students' mathematics learning outcomes. Future research can explore the specific factors in the application of the jigsaw model that have the most influence on improving learning outcomes.